Community Behavior to Prevent Covid-19 and its Associated Factors in North Parigi District - I Kadek Wartana; Veni Mornalita Kolupe; Sitti Fajrah; Rikwan Rikwan; Gustini Gustini (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: The Spread of Covid-19 can be prevented by implementing Covid-19 prevention behavior. This research aims to analyze factors related to covid-19 prevention behavior in the community. Methods: This research was an observational analytical study with a cross sectional design approach in North Parigi District from July until December 2022. Variables in this study include age, gender, occupation, income, education, health insurance, history of covid-19 infection, history of covid-19 vaccination and behavior to prevent covid-19. Sample in this study was 120 people taken by simple random sampling. Data were collected using a questionnaire and analyzed using univariate and bivariate analysis utilizing the Chi Square test. Ethical approval was obtained from Health Polytechnis of Palu, Ministry of Health Indonesia, Number: 0089/KEPK-KPK/VI/2022. Results: The results of this study demonstrated that there was a relationship between age (p=0.000), occupation (p=0.001), history of covid-19 infection and behavior to prevent covid-19. Conclusion: This study concludes that there was a significant relationship between age, occupation, history of covid-19 infection and behavior to prevent covid-19. therefore, the community and health workers can work together, support each other, and follow the guidelines to create a saver and healthier environment from covid-19 for all.